2016
DOI: 10.5194/hess-20-299-2016
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation in environmental systems – Part 2: Catchment mean transit times and young water fractions under hydrologic nonstationarity

Abstract: Abstract. Methods for estimating mean transit times from chemical or isotopic tracers (such as Cl − , δ 18 O, or δ 2 H) commonly assume that catchments are stationary (i.e., timeinvariant) and homogeneous. Real catchments are neither. In a companion paper, I showed that catchment mean transit times estimated from seasonal tracer cycles are highly vulnerable to aggregation error, exhibiting strong bias and large scatter in spatially heterogeneous catchments. I proposed the young water fraction, which is virtual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(230 citation statements)
references
References 34 publications
6
206
2
Order By: Relevance
“…The results presented here suggest that nonstationarity (which is, very loosely speaking, heterogeneity in time) is likely to create its own aggregation bias, in addition to the spatial aggregation bias identified here. This aggregation bias can also be characterized using benchmark tests, as I show in a companion paper (Kirchner, 2016).…”
Section: Other Methods For Estimating Mtts From Tracersmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented here suggest that nonstationarity (which is, very loosely speaking, heterogeneity in time) is likely to create its own aggregation bias, in addition to the spatial aggregation bias identified here. This aggregation bias can also be characterized using benchmark tests, as I show in a companion paper (Kirchner, 2016).…”
Section: Other Methods For Estimating Mtts From Tracersmentioning
confidence: 99%
“…One would expect F yw to increase under wetter conditions, as the water table rises into more permeable near-surface zones and as the flowing channel network extends to more finely dissect the landscape (Godsey and Kirchner, 2014), thus shortening the path length of subsurface flows as well as multiplying the wetted catch-ment area in riparian zones. In a companion paper (Kirchner, 2016), I show that young water fractions can be estimated separately for individual flow regimes, allowing one to infer how shifts in hydraulic forcing alter the fraction of streamflow that is generated via fast flowpaths. I further demonstrate how one can estimate the chemistry of "young water" and "old water" end-members, based on comparisons of F yw and solute concentrations across different flow regimes.…”
Section: Potential Applications For Young Water Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted our investigation by combining two dissimilar water components in virtual experiments and comparing the true mixed MTTs with the tritium-inferred apparent MTTs, as Kirchner (2016a) did with seasonal tracer cycles. Our experiments did not include examination of non-stationary hydrological systems, for which Kirchner (2016b) had found similar underestimation of MTTs with seasonal tracer cycles. We also examined aggregation effects for young water fractions estimated using tritium.…”
Section: Introductionmentioning
confidence: 99%
“…Kirchner (2016b) suggested that the young water fraction is robust against nonlinear effects when 20 considering seasonal amplitude differences. It may happen that * values are similarly robust but this would require further investigation.…”
Section: Discussionmentioning
confidence: 99%